Pengaruh Kekuatan Aspal dengan Penambahan Serbuk Abu Bata sebagai Pengganti Filler pada Lapisan AC-WC dan AC-BC - Hermansyah Hermansyah; Hamka Hamka; Imam Fadly (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Road construction using aggregates. In Pinrang, the material used to make samples was brick ash. The aim of this research is to determine the aggregate properties and aggregate compatibility of AC-WC dan AC-BC asphalt concrete mixtures based on general specifications from Marga Buildings in 2018. This study, which was carried out in the laboratory from August to October 2023, used an experimental approach. According to the research results, the AC-WC dan AC-BC stability value obtained from adding 5% brick ash content with 5% asphalt content was 1975.31 kilograms and 6% asphalt content was 2995.74 kilograms. The MQ value is 833.46 Kg/mm 5%, and 6% 1109.53 Kg/mm, while the stability value obtained by adding 6% brick ash content with 5% asphalt content is 1564.59 kilograms and 6% asphalt content is 2399 .03 kilograms. The MQ value is 665.78 Kg/mm for 5% and 6% 891.83. The AC-BC stability value obtained from 5% brick ash with 5% asphalt content is 2023 ki.29 kilograms and 6% The large asphalt content is 2018.77 kilograms, the resulting MQ value is 613.12 from 5% and 6% is 531.25. The stability value resulting from the addition of 6% brick ash with 5% asphalt content is 1118.02 kilograms and 6% is 1122 .54 and the resulting MQ values were 272.69 from 5%, 267.27 from 6%. From the results of this research, the addition of 6% brick ash can reduce the stability of AC-WC and AC-BC, in contrast to 5% brick ash increasing stability.